THE KALKARINDJI CONTINENTAL FLOOD BASALT PROVINCE: A NEW CAMBRIAN LARGE IGNEOUS PROVINCE IN AUSTRALIA WITH POSSIBLE LINKS TO FAUNAL EXTINCTIONS - Glass L.M.; Phillips D. (My University, 2006)
Extensive basaltic volcanism (>106 km2) occurred across northern and western-central Australia during Cambrian time. The basalts are geochemically distinctive, having unusually uniform elevated incompatible element signatures (high Th/U, La/Sm, Rb/Ba) that are atypical of most other continental flood basalt provinces. Individual volcanic and intrusive suites previously assigned to local stratigraphic units are shown to share a common parental magma. This vast Cambrian igneous province is here named the Kalkarindji continental flood basalt province, Australia's oldest and largest Phanerozoic large igneous province. High-precision 40Ar/39Ar analyses of plagioclase feldspar separates from basalt flows yield ages of 508 ± 2 Ma and 505 ± 2 Ma (2σ), indistinguishable from previous U-Pb zircon ages for related dolerites. These ages indicate that basaltic volcanism coincided with the Early-Middle Cambrian boundary and suggest a temporal link between eruption of the Kalkarindji basalts and the end-Early Cambrian (early Toyonian) faunal mass extinction event. © 2006 Geological Society of America.
Keywords: AR DATING; AUSTRALIA; CAMBRIAN; FLOOD BASALT; MASS EXTINCTIONS; PLAGIOCLASE; Paleozoic::Cambrian; Палеозой::Кембрийская